18F-Fluorodeoxy Glucose and 11C-Methionine Accumulation in Demyelinating Lesions - Noriaki Tomura; Toshiyuki Saginoya; Chikako Kaneko (World Journal of Nuclear Medicine)
Background Few studies have evaluated the accumulation of 18F-fluorodeoxyglucose (FDG), 11C-methionine (MET), and other positron emission tomography (PET) tracers in patients with demyelinating disease. Purpose This study aimed to investigate the accumulation of FDG-PET/computed tomography (CT) and MET-PET/CT in demyelinating lesions. Material and Methods A retrospective search of the patient database in our hospital identified five patients with demyelinating disease in whom PET studies performed in the past 10 years revealed accumulation of FDG or MET. The clinical diagnoses were multiple sclerosis (n=1), myelitis (n=1), limbic encephalitis (n=1), chronic inflammatory demyelinating polyneuropathy (CIDP; n=1), and acute demyelinating encephalomyelitis (ADEM; n=1). Two patients received FDG-PET/CT alone and three patients received both FDG-PET/CT and MET-PET/CT on the same day. Images were visually and conjointly reviewed by two radiologists. In semiquantitative evaluation, the maximum standardized uptake value (SUVmax) of the lesion was measured. The lesion-to-normal brain uptake ratio (L/N ratio) was calculated. Results FDG and/or MET accumulated to a part of the lesions seen on MRI. SUVmax on FDG-PET/CT ranged from 3.8 to 10.3, and L/N ratio on MET-PET/CT ranged from 16.6 to 2.4. Conclusion It has been established that neoplastic and demyelinating lesions can be differentiated on the basis of FDG or MET uptake. However, as accumulation of FDG and MET can also occur in demyelinating lesions; knowledge of this possibility is of clinical importance.